2021
DOI: 10.1007/s12036-021-09718-2
|View full text |Cite
|
Sign up to set email alerts
|

Sub-MeV spectroscopy with AstroSat-CZT imager for gamma ray bursts

Abstract: Cadmium-Zinc-Telluride Imager (CZTI) onboard AstroSat has been a prolific Gamma-Ray Burst (GRB) monitor. While the 2-pixel Compton scattered events (100-300 keV) are used to extract sensitive spectroscopic information, the inclusion of the low-gain pixels ( $ 20% of the detector plane) after careful calibration extends the energy range of Compton energy spectra to 600 keV. The new feature also allows single-pixel spectroscopy of the GRBs to the sub-MeV range which is otherwise limited to 150 keV. We also intro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Singhal et al (2021) used the same older version to measure fluxes of bright sources by the earth occultation technique. (Chattopadhyay et al 2021) demonstrated the validity of the mass model simulations for spectroscopic analyses, using this current mass model version.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Singhal et al (2021) used the same older version to measure fluxes of bright sources by the earth occultation technique. (Chattopadhyay et al 2021) demonstrated the validity of the mass model simulations for spectroscopic analyses, using this current mass model version.…”
Section: Discussionmentioning
confidence: 78%
“…Using an older version of this mass model with minor differences, a satisfactory agreement in spectral parameters between Fermi and CZTI was reported in Chattopadhyay et al (2019) for GRB 160821A. Chattopadhyay et al (2021) used this latest version of the mass model to expand the work to eleven bright GRBs detected in the first year of CZTI operation and showcases capability of CZTI as a sub-MeV spectrometer, and thereby validating this AstroSat-CZTI mass model further.…”
Section: Spectral Comparisonsmentioning
confidence: 91%
See 2 more Smart Citations
“…Another challenge is to calibrate these pixels in the absence of any mono energetic lines at energies above 100 keV to estimate their gains. A careful calibration of these pixels have been attempted in a companion paper by Chattopadhyay et al (2021) in this issue, and spectroscopy up to 900 keV is explored for Gamma Ray Bursts (GRBs). Compared to the ON-axis sources, spectroscopy of GRBs is relatively easy because of the availability of background (from the immediate pre-GRB and post-GRB observations) and the significantly higher signal to noise ratio for the GRBs.…”
Section: Introductionmentioning
confidence: 99%